Stability and Hopf Bifurcation Analysis of a Gene Expression Model with Diffusion and Time Delay - Yahong Peng; Tonghua Zhang (Abstract and Applied Analysis)
We consider a model for gene expression with one or two time delays and diffusion. The local stability and delay-induced Hopf bifurcation are investigated. We also derive the formulas determining the direction and the stability of Hopf bifurcations by calculating the normal form on the center manifold.